Phytoplankton community structure in floating cages area in the Koto Panjang Dam, Kampar Regency, Riau Province - Mahadi Hasan; Eni Sumiarsih; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe aquatic environmental condition of the Koto Panjang Dam has been changed due to the presence of floating net cages (FNC) activities and this condition may affects the phytoplankton presence in that area. A research aims to understand the structure of the phytoplankton community around the floating net cages in the Koto Panjang Dam has been conducted in Oktober-Desember 2019. There were three different stations. Samplings were conducted 3 times, once/week. Results shown that were 25 species of phytoplankton present, such as Chorella sp, Microcystis sp, Cosmarium tintacum, Achnants sp and Euglena sp. The phytoplankton abundance was ranged form 19,250 – 29,750 cells/L (mesotrophic). The diversity index (H’) was 3.48 – 3.74 (high). The simillarity index (E) 0.09 was low. The dominance index (C) was 0.45 – 0.53 (low). Data obtained indicate that the water quality arround the FNC is good and it may able to support the life of phytoplankton.Keyword: water quality, abundance, diversity index, simillarity index, dominance index